AI-Generated Feedback in English Writing: Proficiency Development and Learner Perceptions - Wang, Jian; Zhang, Xiaohong (English Language Education, Universitas Internasional Batam, 2025)
This study was situated within the context of college-level English-as-a-foreign- language education in China. It compared the effectiveness of AI-generated feedback and teacher feedback in improving English learners’ writing proficiency. A questionnaire survey and semi-structured interviews were also conducted to examine learners’ acceptance of and attitudes toward AI feedback. Results revealed that both the experimental group (receiving AI feedback) and the control group (receiving teacher feedback) showed significantly higher post-test scores compared to their pretest scores. Although the mean difference in post-test scores between the two groups exceeded that of the pretest, no statistically significant difference was found in their final performance, suggesting comparable efficacy between AI feedback and teacher feedback in enhancing writing proficiency. Additionally, the experimental group demonstrated moderate acceptance of AI feedback, with perceptions varying across proficiency levels. However, learners universally agreed that combining teacher feedback and AI feedback would yield greater benefits for writing development. The study concludes that both feedback modalities have distinct benefits and misfits, advocating for their integrated—rather than exclusive—use in writing instruction.